Transcortical Approach to Deep-Seated Intraventricular and Intra-axial Tumors Using a Tubular Retractor System: A Technical Note and Review of the Literature - Okasha, Mohamed; Ineson, Georgia; Pesic-Smith, Jonathan; Surash, Surash (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background Retraction of white matter overlying a brain lesion can be difficult without causing significant trauma especially when using traditional methods of bladed retractors. These conventional retractors can produce regions of focal pressure resulting in contusions and areas of infarct.Methods In this article, we present a retrospective case series of six patients with deep-seated intraventricular and intra-axial tumors that were approached using a ViewSite Brain Access System (tubular retractor). The authors describe a unique method of creating a pathway using a dilated glove. We shall also review the relevant literature that reports this type of surgery. Cases included three cases with third ventricular colloid cysts, one case of a third ventricular arachnoid cyst, one case with a lateral ventricular neurocytoma, and a case with a deeply seated intra-axial metastatic tumor.Results Gross total resection was achieved in five cases with small residual in the central neurocytoma operation, with no documented neurological deficit in any case. One case had persistent memory problems and one case had continuing decline from the metastatic disease.Conclusion The introduction of tubular-shaped retractor systems has offered the advantage of reducing retraction pressures and distributing any remaining force in a more even and larger distributed area, thus reducing the risk of previous associated morbidity while also permitting great visualization of the target lesion.
Keywords: tubular retractor; intraventricular tumors; colloid cyst; minimal invasive surgery; balloon dilatation